STUDY ON THE AXIAL BEARING CAPACITY OF T AEROSTATIC BEARING - ZHAO Gong; WANG BaoRui; YANG Hong; CUI HaiLong (Jixie qiangdu)
Even a small axial vibration or an axis deflection vibration of the aerostatic bearing of DFC tool can be quite significant for ultra-precision machining. It is of great importance to obtain the accurate axial bearing characteristic（ bearing capacity and thrust stiffness） during its design,parameter optimization,machining and using process. However,there exists many error terms in the engineering practice to test the axial bearing capacity（ thrust bearing capacity） of T aerostatic bearing,such as, the machining error, effect of environment factors（ temperature, humidity, etc.） on the micro-displacement measurement device,deformation and deflection of the structure itself during the loading process,etc. All these lead to a large error between the measurement stiffness value and the actual value. Based on these problems,this article studied the axial bearing capacity（ thrust bearing capacity） of T aerostatic bearing by means of finite element simulation. Meanwhile,the influence of orifice number and air supply pressure on the axial bearing capacity（ thrust bearing capacity） of T aerostatic bearing is also studied and the accuracy of the simulation results has been validated by the carried out experiment.